Performance of stone mastic asphalt mixture reinforced with newly developed interlocking chained plasti-beads - Ahmad, Nadzrol Fadzilah (2014)
Stone Mastic Asphalt (SMA) is a gap-graded hot mixture consisting of a coarse aggregate skeleton and high binder content. Typical standard and specification of void in mineral aggregate (VMA) for this type of mixture range between 16 to 18%. Aggregate with 3 to 8mm diameter size found to be the largest portion that form a matrix skeletal in SMA mixture. The objective of this study is to develop and design Chained Plasti-beads (CPB) that utilize the VMA existence in SMA mixture as an interlocking mechanism and to evaluate their potential in resisting fatigue failure of Stone Mastic Asphalt. The research was undertaken in four stages. The first stage of the study was carried out on develop Chained plasti-beads (CPB); this includes designing the shape configuration and dimensions (bead size, shape, chained spacing and thickness) to suit the void spaces in asphalt mixture. The second stage was to evaluate and analysis the CPB physical and mechanical properties. The third stage was to determine and justify the suitable quantity of CPB to be replaced for some portion of aggregate in mixture on volume bases, while the fourth stage devoted to fabrication and testing of fatigue beam specimens using Repeated Flexural Beam Fatigue in accordance with AASHTO TP8-94 321 to investigate the potential prospects to enhance asphalt mixture fatigue cracking properties by means of flexural beam fatigue test. In this study, CPB of 4mm and 6mm diameter diamond shaped beads with 0.5mm and1.0mm thick chained beads link (M4/0.5, M4/1.0 and M6/0.5, 6M/1.0) with spacing between beads set at 20mm interval was developed and designed mainly to act as reinforcement to increase the tensile strength when pavement subjected to traffic loading. The interlocking mechanism through VMA concept was adopted using replacement strategy of some portion of aggregate sizes (2.3 – 4.75mm) by CPB on volume bases as such three different contents (0.5%, 1.0% and 1.5%) of CPB were selected and used throughout the study. SMA beam specimens were prepared with the above CPB sizes and proportions and tested to simulated loading and temperature conditions in accordance with ASTM and AASHTO Standards. Laboratory repeated flexural fatigue bending beam tests were conducted at five different strain levels (350 to 650μm) represents low, medium, and high traffic loading to evaluate the incorporation of CPB in SMA to assess mixture fatigue cracking performance. Two new concepts of analysis; Stress Loss Ratio (SLR) and Fatigue Resistance Ratio (FRR) along with stiffness reduction and energy ratio concepts were used to determine the significant CPB combinations that serve as an interlocking mechanism through VMA concept and to evaluate fatigue cracking potential. At 350 micro-strain (με) loading; CPB M4/0.5, M4/1.0 and M6/0.5 specimens showed significant improvement in terms of fatigue resistance and stiffness compare to control specimens. In general, most analyses approaches used in this study revealed, as the strain level increased, the fatigue resistance trend of CPB mixture decreased gradually and the performance showed almost the same trend at higher strain level of 650με. M6/1.0 specimens performed the worst compared to the other CPB specimens.